Transformasi Sosial Melalui Lensa Teologi: Memahami Peran Agama Dalam Mengatasi Ketimpangan Sosial Pada Konteks Kontemporer - Heni Maria; Intan Laurens; Hantrini Patoo; Alfriani Sapa (STT Kingdom, 2023)
This paper discusses the role of religion in overcoming social inequality in a contemporary context. Social inequality is a complex and deep issue involving aspects such as economic, political, cultural and social. In seeking solutions to these inequalities, religion often has an important role to play in shaping societal views of well-being, justice and human relations. This study uses a theological approach to analyze the contribution of religion in overcoming social inequality. Through theological understanding, this paper will identify the values ??that underlie religious teachings that can be a source of inspiration and motivation for social transformation. First, this paper will explain the understanding of social inequality in the contemporary context, including its causes and impacts on society. Then, the focus will shift to the role of religion in helping to overcome this social inequality. Furthermore, this paper will analyze theological perspectives from various religions regarding social issues such as poverty, economic inequality, gender differences, and human rights. Through exploring sacred texts and religious doctrines, the author will highlight universal values ??that inspire and motivate religious people to act in overcoming social inequality.